Life cycle cost of electricity generation from rice straw in Malaysia: Sensitivity analysis of economic performance - Mohd Shafie, Shafini (School of Technology Management and Logistics (STML), 2019)
The limited availability of fossil fuel as a feedstocks is among the key causes for the current transitions toward the use of biomass energy. Alongside the environmental and energy concerns, the economic sustainability of biomass initiatives are considered as key factors in the future development of this sector (Fazio & Barbanti, 2014). Hence, economic analysis on biomass power generation would assess its long-term profit and increase its share in energy mix. According to (Jungingera et al., 2006), however, the high production costs are affecting biomass potential if compared with fossil fuel. Among the prevailing types of agriculture residues utilized as biomass for electricity production, rice straw notably differentiates itself from other biomass fuels, such as wood, wood residues, and palm oil residues. For example, many researchers are carrying out analyses on the utilization of palm oil residues in power generation. Since the costs of biofuel input mostly depend on the type of biomass resource and its location (Lu¨ schen & Madlener, 2013), therefore paddy residues have been analysed in this paper as feedstocks in electricity generation.